Mood recognition through facial expression and speech cues - Tan, Jonathan Tian-Ci (2014)
Emotion interpretation is important to allow one to comprehend his or her environment. Knowing the emotional state of the surroundings can influence the decision-making process. Previous work has shown that both Facial Expressions and Vocal Data can be used to determine the emotions of a person. The systems relied on a unimodal approach, which only focused on one aspect. However, the accuracy for emotion recognition was low, and there was a vital reliance on specific hardware.